Gene frequencies of human platelet antigens in the Macedonian population - M. Pavkovic; A. Petlichkovski; A. Strezova; T. Arsov; D. Trajkov; M. Spiroski (Wiley Online Library, 2006)
Human platelet antigen (HPA) systems consist of more than 12 bi-allelic antigen polymorphisms. Due to these polymorphisms, platelet-membrane glycoproteins can be recognized as alloantigens or autoantigens and can cause conditions such as fetomaternal alloimmune thrombocytopenia, post-transfusion refractoriness to platelets, and post-transfusion throbocytopenic purpura. The purpose of this study was to investigate the distribution of HPA-1, -2, -3, and -5 in Macedonian population by using the polymerase chain reaction and restriction fragment length polymorphism. The allele frequencies were 0.865 for HPA-1a, 0.135 for HPA-1b, 0.852 for HPA-2a, 0.148 for HPA-2b, 0.578 for HPA-3a, 0.422 for HPA-3b, 0.909 for HPA-5a, and 0.091 for HPA-5b. Results of our study were not significantly different from those reported in the other European studies. Our population displayed the highest frequency for HPA-2b allele (0.148) reported among European population.